Festivals, theater and political field at Athens in the fifth century BC - Moerbeck, Guilherme (Romanitas - Revista de Estudos Grecolatinos, 2013)
This article is aimed to evaluate the role of the Great Dionysia along the political celebrations in Athens, during the fifth century BC. For this, we take the notion of the political field, developed by the sociologist Pierre Bourdieu. It is also emphasized, the most important liturgy of that festival: the choregia. Besides, we analyze some fragments of tragedies that were performed at a specific time of the celebrations for Dionysius, such as: Euripides’ Phoenissae and Sophocles’ Oedipus at Colonus.